(3GdMeGjI GdLfGFjI ddeMQQGJ GdEdcJQhfjI (B: s (3OQGSI ebGQfI (B/ s - (3CMeO YGUe CMeO YLjdgs; (3YeQ eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2013)
(3JJfGhd GdOQGSI GdMeGjI GdLfGFjI ddeMQQGJ GdEdcJQhfjI, adbO COQc GdLejY Cf GdMbjbI eSWhQI HGdcJGHI COYi Edi GdKbI h CHbi Ydi eQ GdYUhQ , agPG Gdce GdeJOab ef GdeYdheGJ h GdHjGfGJ YUi Yf GdEOQGc eG de JTedg hSGFd GdMaX h GdJNRjf aj GdeMQQGJ GdEdcJQhfjI, hef gfG JHOh CgejI GdeMQQGJ GdEdcJQhfjI aj GdJjSjQ Ydi GdCaQGO HMaX JYGedGJge h EKHGJ JUQaGJge GdbGfhfjI, hgh eG LYd abgGA GdbGfhf GdLfGFj jVYhf gGdI cHjQI ef GdCgejI HGdfSHI ddMeGjI GdLfGFjI dJdc GdeMQQGJ(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj (B2013.s
(3HHdjhLQGajG(B: (3UaMGJ (B653-689.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdeMQQGJ GdEdcJQhfjIs; (3GdMeGjI GdLfGFjIs; (3CQcGf LQGFe GdeMQQGJ GdEdcJQhfjIs; (3GdMeGjI GdLfGFjI GdehVhYjI ddeMQQGJ GdEdcJQhfjIs; (3GdWHjYI GdbGfhfjI ddeMQQGJ GdEdcJQhfjs; (3eGgjI GdeMQQ GdEdcJQhfjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs